2018
DOI: 10.1002/cam4.1595
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model, including the EBV status of tumor cells, for primary gastric diffuse large B‐cell lymphoma in the rituximab era

Abstract: EBV‐positive diffuse large B‐cell lymphoma (DLBCL), not otherwise specified (NOS), often affects the gastrointestinal tract. However, the prognostic significance of EBV associated with primary gastric DLBCL (gDLBCL) has not been established. This retrospective study included 240 patients with primary gDLBCL, diagnosed between 1995 and 2015. Tumor specimens were analyzed with EBER in situ hybridization. In 25 (10%) cases, tumor cells harbored EBV. The EBV + group more frequently exhibited programmed death‐ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 38 publications
3
37
1
Order By: Relevance
“…EBV + iDLBCL and nPD‐L1 + cases were characterized by an aggressive clinical course in this series. In addition, patients with de novo CD5 + DLBCL tended to have a worse prognosis than CD5‐negative cases, which is in agreement with Yamaguchi et al In our previous report on primary gastric DLBCL (gDLBCL), miPD‐L1‐negativity (<20%) and CD5 positivity were not confirmed to have poorer outcomes in contrast to iDLBCL, whereas EBV harboring on tumor cells was an independent adverse factor in both the gDLBCL and iDLBCL series . Notably, none of the gDLBCL cases examined in our series expressed PD‐L1 on tumor cells.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…EBV + iDLBCL and nPD‐L1 + cases were characterized by an aggressive clinical course in this series. In addition, patients with de novo CD5 + DLBCL tended to have a worse prognosis than CD5‐negative cases, which is in agreement with Yamaguchi et al In our previous report on primary gastric DLBCL (gDLBCL), miPD‐L1‐negativity (<20%) and CD5 positivity were not confirmed to have poorer outcomes in contrast to iDLBCL, whereas EBV harboring on tumor cells was an independent adverse factor in both the gDLBCL and iDLBCL series . Notably, none of the gDLBCL cases examined in our series expressed PD‐L1 on tumor cells.…”
Section: Discussionsupporting
confidence: 87%
“…These cases indicate that EBV + iDLBCL preferably arises among patients with previous history of lymphoma or immunosuppressive drug treatment and is less common in immunocompetent individuals. These findings were not replicated in our recent series of 25 EBV + gastric DLBCL cases . The striking features of EBV + iDLBCL might highlight the specificity of the intestine as a preferred anatomical site affected by immunodeficiency‐associated LPDs.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Similar to our results, Lin et al also demonstrated that a better ECOG performance status was related to better PFS and OS by enabling more intensive chemotherapy regimen and adequate cycle of chemotherapy to be performed in patients with DLBCL [18]. Furthermore, in line with previously published results [19,20], multiple gastric https://doi.org/10.1371/journal.pone.0238807.g003 lesions were also identified for LRFS (HR, 6.59; p<0.001), PFS (HR, 4.04; p = 0.005), and OS (HR, 7.63; p = 0.001). For instance, Liu et al reported that multiple gastric lesions were an independent adverse prognostic factor of OS (p = 0.011) [19].…”
Section: Plos Onesupporting
confidence: 91%
“…Previous studies have described several features that served as prognostic indicators of poor clinical outcome in PG-DLBCL, including deficiency of gene translocation involving the immunoglobulin heavy chain [12], Helicobacter pylori negativity [13], Lugano stage II2/IIE/IV, elevated serum LDH level [14], and Epstein-Barr virus infection [15]. Due to the marked heterogeneity of DLBCL, a reliable prediction tool is vital for optimizing patient treatment.…”
Section: Discussionmentioning
confidence: 99%